Synthesis and biological evaluation of novel drug-monoclonal anti-carcinoembryonic antigen antibody immunoconjugates - Lau, Achilles K. M., 1965- (1994)
Thesis (M.Sc.)--Memorial University of Newfoundland, School of Pharmacy, 1995. Pharmacy Bibliography: leaves 206-228. In Process